Knowledge and perceptions of government officials on public policy: the case of the Population Policy for South Africa - Frade, Sasha (My University, 2013)
South Africa has had a long history of policies that have been geared towards trying to limit the size and distribution of certain population groups. The International Conference on Population and Development (ICPD) in Cairo in 1994 coincided with the first democratic elections in the country. Since 1998, however, implementation by key stakeholders (each of which were given implementation responsibilities) has not been uniform. Reasons for failure to fully and effectively implement the policy must be explored and understood. This study used both qualitative and quantitative interviews to explore possible factors that could have led to implementation failure. Two semi-structured interviews were conducted with experts. Information gathered from the qualitative interviews guided the creation of the structured questionnaire. Interviews at the end of the data collection phase were conducted in order to explore the results of the quantitative interviews and gain a more in-depth understanding of the issues and results that arose. The research shows that respondents of the questionnaire and the national and provincial interviewees did not have sufficient knowledge of the policy, and the process that led to its formulation and implementation. Development agencies, and specifically the UNFPA, had a pivotal role in influencing the ideas behind the policy. Only those that work in departments that directly work with people find value in the Population Policy. Incorporation of statistics into policy formulation seems to be limited, and used only for reporting purposes. Even the Population Policy itself was drafted without having statistics on South Africa. None of the respondents stated that they were a member of the Population Association of South Africa (PASA), had participated in the Applied Population Sciences Training and Research (APSTAR) or the Population, Environment and Development (PED) courses (which at the time of the interview had only had 670 officials complete the course). One of the reasons that this policy has not achieved all of its stated objectives is the fact that it is supposed to be implemented at different levels of government. This complicates implementation by creating a long chain from national to local level activities. Sasha Frade – 0200123J Page 8 A short and summarised version of the background, importance and objectives of the Population Policy should be made available to government departments. This would need to be done by the Population Unit, but a person or group of people within each department could be assigned with the responsibility of assuring monitoring and evaluation. Together with measureable indicators a revised population policy may be easier to monitor in the long term. This could be incorporated in the government-wide Monitoring and Evaluation System. Finally, government departments and officials must be made aware of the importance of statistics to plan programmes and strategies.
MM (P&DM) thesis
Keywords: Population policy - South Africa; Population